Evaluation of the method of gingivectomy done in endodontically treated teeth - MARIONA, PREETHI; KAREEM, NASHRA; DHARMAN, SREEDEVI (The journal of contemporary issues in business and government, 2021)
Gingivectomy is done to correct gingival levels , esthetic contour and adequate crown length which is required. Gingivectomy is a type of clinical crown lengthening. The tooth requiring endodontic treatment requires Clinical crown lengthening procedure because of overgrowth of gingiva. Gingivectomy can either be done using a scalpel or laser depending on the procedure. The study aims at evaluating the gingivectomy method done in endodontically treated teeth. The details of patients requiring CLP/gingivectomy prior to RCT were collected.72 patients required the procedure. The details of these patients were collected and reviewed. Excel tabulation was done, results and graphs were obtained from SPSS. Statistical test performed was the Chi square test. 52.76% of the total underwent laser gingivectomy whereas 47.22% of them underwent laser gingivectomy. Chi square test shows p>0.05, non significant association. Thus it was found that the patients requiring gingivectomy prior to endodontic treatment had mostly undergone laser gingivectomy than surgical gingivectomy.